Importance of Anti Retro Viral Therapy - Humsafar Trust; Sahyog (My University, 2019)
This film documents the narratives of people from the LGBTQ+ community who are HIV positive. It Highlights the importance of medications and counselling for people with HIV, so that they can lead a better life.
Keywords: People from LGBTQ Community Living with HIV